The Effect of Double D Method on Post Partum Depression Levels in post partum Mothers Phase Letting Go in Wonokromo Village Surabaya - Maimunah, Siti; Masita, Elly Dwi (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
Women had high risk to be postpartum depression attacks. Postpartum depression is described as a non-psychotic disorder in the form of mood disorders and self-confidence lasting for up to one year (Almond, 2009; Apter, Devouche, Gratier, Valente, & Nestour, 2012). In the western states the incidence of postpartum depression reaches 10- 20% while the share of developing countries reaches> 20%. This condition will affect the social status of mothers, disorders of self-confidence, comfort disorders and even have the intention to commit suicide and disruption of child development both intelligence, social and psychology (Hansotte, Payne, & Babich, 2017). A preliminary study conducted in March 2018 in the Wonokoromo sub- district found that 45% of postpartum mothers had postpartum depression at mild and moderate levels. The purpose of this study was to determine the differences in the degree of postpartum depression between the control group and the treatment group after being given a double D method (dhikr and prayer). This type of research is quasi-experimental quantitative analysis with EDPS questionnaire instrument (Edinburgh Depression Postpartum Scale). The sampling used was purposive sampling by determining the inclusion criteria which amounted to 84 respondents by dividing 42 respondents as the control group and 42 respondents as the treatment group. Analysis test used was Mann Whitney with a value of p <0.005. The results of the analysis test obtained p = 0.001 which means that there was a significant difference in the level of postpartum depression between the control group and the treatment group after being given a double D method (dzikir and prayer) in postpartum mothers in the letting go phase (day 7). Conclusion: The double D method was effective in reducing postpartum depression in postpartum mothers in the letting go phase.